Women of the four winds - Olds, Elizabeth Fagg. 4 0 16; 5 (Boston : Houghton Mifflin, 1985)
Biographies of four of America's first women explorers: Annie S. Peek, Delia J. Akeley, Marguerite Harrison and Louise A. Boyd. Louise Boyd made numerous trips through the Arctic, including Spitzbergen, Franz Josef Land and the fiords of east Greenland. Marguerite Harrison made trips across Siberia.
Annie Smith Peck -- Delia J. Akeley -- Marguerite Harrison -- Louise Arner Boyd.
Includes bibliographical references (p. 299-305) and index.
Keywords: 2 -- 0; 6; Women explorers;Explorers -- United States -- 20 -- Biography.;Biography.; 20; 2